Effect of iron supplementation in healthy exclusively breastfed infants: a systematic review and meta-analysis - Tian, Ke; Liu, Wenli; Huang, Yi; Zhou, Rong; Wang, Yan (Frontiers in Pediatrics, 2025)
Background and objectivesExclusively breastfed infants are at risk of iron deficiency due to the low iron content in breast milk. This study aims to evaluate the benefits and risks of daily oral iron supplementation on growth, cognitive outcomes, and hematologic parameters in these infants.MethodsData sources include Cochrane Central Register of Controlled Trials, PubMed, and Embase from inception to December, 2024. Randomized controlled trials were included. The Cochrane risk of bias tool was used to assess the methodological quality of included trials. The continuous outcomes were analyzed by calculating the mean difference (MD) and the binary categorical variables were analyzed using relative risk (RR) with 95% confidence intervals (CI).ResultsThis study included 8 trials (685 participants) comparing iron supplementation to no iron. At 6 months of age, compared to infants who were exclusively breastfed without iron supplementation, those who received oral iron supplementation showed an increase in hemoglobin (Hb) levels (MD 0.42, 95% CI 0.19–0.66, p < 0.001, I2 = 76%) and a reduction in the incidence of iron deficiency (ID) (RR 0.38, 95% CI 0.15–1.00, p = 0.050, I2 = 29%) and iron-deficiency anemia (IDA) (RR 0.58, 95% CI 0.40–0.84, p = 0.004, I2 = 0). However, by 12 months of age, the supplementation had no effect on Hb levels, ID, the incidence of IDA or mental development index (MDI). Iron supplementation appeared to reduce weight gain (MD = −0.04, 95%CI −0.07 to −0.01, p = 0.004, I2 = 0) and head circumference gain (MD = −0.14, 95% CI −0.18 to −0.09, p < 0.001, I2 = 25%).ConclusionsLimited available evidence suggests that iron supplementation is beneficial for hematologic parameters and the incidence of IDA in healthy exclusively breastfed infants. However, it may delay weight gain and head circumference growth.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, PROSPERO [CRD42024610082].